Diseño e implementación de un sistema de monitoreo y adquisición de datos de parámetros eléctricos y ambientales de un sistema fotovoltaico conectado a la red de 3kW - Cruz, Edisson (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
In the present research work, a wireless monitoring and data acquisition system with an interface in LabVIEW was designed and implemented in real-time to monitor the electrical and environmental parameters of a 3kW SFCR. cable integrating devices such as a Raspberry pi 3B+, an Arduino Nano, using a 03 PT100 temperature sensor, a voltage divider as a voltage sensor, ACS758 current sensor, a calibrated cell as an irradiance sensor, and a graphics and storage interface From the data of a program developed in LabVIEW, the model and 3D printing of the pieces of the carcass can also be implemented, thus implementing a prototype with a DIN holder. Everything is oriented according to the IEC-61724-2017 standard. In the period of 05 days, it gives us the following results: Influence of the temperature in the photovoltaic module, in which we were able to observe that the temperatures of each cell in the module are not the same, having a deviation of up to 3C which it causes lost by dispersion of parameters. Influence of the temperature on the photovoltaic generator, in which we could observe that the temperature and the voltage in a photovoltaic system are inversely proportional, and when the hottest is a photovoltaic module is less efficient, in this section, temperatures up to 52.31C were recorded. the surface of the photovoltaic module. Influence of the irradiance on the photovoltaic generator, apart from which we observed that the irradiance and the generated current are directly proportional, events of extreme solar irradiance were also present, being higher and less prolonged on June 17, 2021, with a value of 1245.89[W/m2], a duration of 06 seconds, recorded at 11:39:13 and the longest, presented the same day, with a value of 1219.75[W/m2], a duration of 176 seconds recorded at 11:34:17 seconds. Finally, it is concluded that the indicators provided on the energy generated by the SFRC under certain environmental conditions are reliable due to the guidelines with the proposed standard, calibration, and validation of the readings of the sensors and other components used.